Dexmedetomidine plus propofol with propofol alone in terms of discharge readiness gynaecological surgeries - Mehmood, Hamid; Navishta Sahar Arif; Asad Khan (Medical Journal of South Punjab, 2024)
Objective: to compare the dexmedetomidine plus propofol with propofol alone in terms of discharge readiness gynaecological surgeries.Methodology: Totally, 60 adult females belonging to American Society of Anesthesiologists (ASA) physical status I and II undergoing minor gynaecological surgeries under general anaesthesia were randomly allocated to receive 1 ?g/kg dexmedetomidine (Group DP) plus propofol, 1 mg/kg propofol, and propofol (Group P) as premedication. Propofol 1% was used for induction and maintenance of anaesthesia keeping BIS between 55 and 70. After the procedure, patients were assessed primarily for discharge readiness using Modified Post Anaesthesia Discharge Scoring System (MPADSS).The secondary outcomes were Modified Aldrete Score (MAS), total dose of propofol used and haemodynamics.Results: The percentage of patients ready for discharge were 22.5%, and 15% at 1 hour in group DP, and P, respectively (p = 0.275). Median MAS was 5 and 6 respectively for group D, and P immediately post-surgery (p = 0.000). The mean dose of propofol used was 69.75 ± 12.56 mg in group D and 135.25 ± 9.2 mg in group P (p = 0.001). TConclusion:  Combining low-dose dexmedetomidine with propofol for anesthesia during gynecological surgeries resulted in delayed discharge readiness.